Risk Assessment of Investing in Energy Enterprises of the Khatlon Region - Makhmadisuf, Sharifov; Fathulo, Fathullozoda Abdukholiq; Azizullo, Muhammed (Minhaj International Journal of Economics and Organization Sciences, 2022)
In their article, the authors analyzed and studied the issue of assessing investment risk in energy enterprises of the Khatlon region. They noted that in today's conditions, it is expected to attract investments in energy enterprises based on an increase in the level and quality of construction of power plants and a gradual increase in the living standards of the population.